Fibre type composition in the lumbar perivertebral muscles of primates: implications for the evolution of orthogrady in hominoids. Issue 2 (31st October 2013) - Neufuss, J.; Hesse, B.; Thorpe, S. K. S.; Vereecke, E. E.; D'Aout, K.; Fischer, M. S.; Schilling, N.
Abstract The axial musculoskeletal system is important for the static and dynamic control of the body during both locomotor and non‐locomotor behaviour. As a consequence, major evolutionary changes in the positional habits of a species are reflected by morpho‐functional adaptations of the axial system. Because of the remarkable phenotypic plasticity of muscle tissue, a close relationship exists between muscle morphology and function. One way to explore major evolutionary transitions in muscle function is therefore by comparative analysis of fibre type composition. In this study, the three‐dimensional distribution of slow and fast muscle fibres was analysed in the lumbar perivertebral muscles of two lemuriform (mouse lemur, brown lemur) and four hominoid primate species (white‐handed gibbon, orangutan, bonobo, chimpanzee) in order to develop a plausible scenario for the evolution of the contractile properties of the axial muscles in hominoids and to discern possible changes in muscle physiology that were associated with the evolution of orthogrady. Similar to all previously studied quadrupedal mammals, the lemuriform primates in this study exhibited a morpho‐functional dichotomy between deep slow contracting local stabilizer muscles and superficial fast contracting global mobilizers and stabilizers and thus retained the fibre distribution pattern typical for quadrupedal non‐primates. In contrast, the hominoid primates showed no regionalization of the fibre types, similar to previous observations in Homo. We suggest that this homogeneous fibre composition is associated with the high functional versatility of the axial musculature that was brought about by the evolution of orthograde behaviours and reflects the broad range of mechanical demands acting on the trunk in orthograde hominoids. Because orthogrady is a derived character of euhominoids, the uniform fibre type distribution is hypothesized to coincide with the evolution of orthograde behaviours.